Chemical Stem Barriers for the Control of Ants (Hymenoptera: Formicidae) in Vineyards - Addison, A. (South African Journal of Enology and Viticulture, 2017)
Ants significantly reduce the efficacy of biological control of the mealybug Planococcus ficus (Signoret) in vines. Two trials were conducted to find a cost-effective method for ant control that is environmentally friendly, practicable and acceptable in an integrated pest management programme. Thirteen chemical stem barriers were assessed for the control of two ant species, Linepithema humile (Mayr) and Anoplolepis custodiens (Smith), in two field trials during two seasons. Four of the treatments that showed high efficacy in the field trials were also evaluated in two simulated field trials for the control of L. humile and Anoplolepis steingroeveri (Forel) due to high variability in pre-treatment counts that occurred in the field trials. Treatments showing the highest efficacy against L. humile and A. custodiens in field trials were the chlorpyrifos-impregnated band and the terbufos slow-release band. Alphacypermethrin SC at 10 mL/L was effective against L. humile and has subsequently been registered as a chemical stem barrier on vines. The treatment showing the highest efficacy against A. steingroeveri in the simulated field trial was alphacypermethrin SC at 20 mL/L. In the simulated field trial, a decline in ant infestation was observed five to six weeks after application of treatments. The most likely explanation is that chemical stem barriers result in ant mortality, although other reasons for this decline are discussed. It is recommended that suitable bioassay techniques, which expose ants to the treated substrate for a limited period, thereby simulating field conditions, be developed in order to determine if chemical stem barriers result in ant mortality.